Manufacturing engineering education in IIUM - Ali, Mohammad Yeakub; Amin, A. K. M. Nurul; Haque, Md. Mohafizul (2007)
This paper presents how manufacturing engineering curriculum in International Islamic University Malaysia (IIUM) is designed to prepare its graduates fit for manufacturing industry. Since the inception in 1994, IIUM has been preparing its students through specialization in manufacturing engineering and precision machining. After 10 years, the curriculum has been revised thoroughly to fit with the recent trend of globalization of manufacturing engineering. The faculty is cognizant of emerging technologies such as micro and nano manufacturing and has begun to incorporate in its curriculum. In addition, the programme has also adapted the outcome based learning in producing engineers ready for industry practices in the international scene. Seminar presentations are emphasized to develop students’ communication skill. All students must undergo engineering internship training in manufacturing industries to complement and reinforce their knowledge earned in classroom and laboratories.